Five views on sanctification - Dieter, Melvin Easterday; Hoekema, Anthony Andrew, 1913-1988; Horton, Stanley M.; McQuilkin, J. Robertson; Walvoord, John Flipse 1910-2002 (Grand Rapids, MI : Zondervan, 1987)
This unique book brings together in a single, easily understood volume five major Protestant views on the subject of sanctification. Christians generally recognize the necessity for the believer to live a holy, or sanctified, life. But they disagree on what sanctification is and on how it can and should be achieved. The five authors describe and defend their own understanding of the doctrine. Each author writes from an Evangelical perspective, viewing the Bible as the authoritative Word of God and considering a restored relationship to God through faith in Christ to be an individual's greatest need and delight. - Back cover.
The Wesleyan perspective / Melvin E. Dieter -- Responses -- The Reformed perspective / Anthony A. Hoekema -- Responses -- The Pentecostal perspective / Stanley M. Horton -- Responses -- The Keswick perspective / J. Robertson McQuilkin -- Responses -- The Augustinian-dispensational perspective / John F. Walvoord.
Includes bibliographical references and indexes.
Keywords: Sanctification